Intercultural Dialogue as Rhetorical Means of Forming of Multilingual Personality - Zagorodnova, Viktoria; Panova, Natalia; Nischeta, Volodymyr; Нreb Mariia (Journal of History Culture and Art Research, 2019)
The state and conditions of functioning of the Ukrainian language and languages of national minorities in Ukraine have led us to think about finding ways to balance the complex sociolinguistic situation in the country. In this regard, it is no coincidence the direction of modern linguadidactics on communicative and functional learning of designated languages in establishments of secondary education with multiethnic contingent of students. The social role of dialogue, connected with change of socio-cultural connections and cultural codes is becoming more and more important. The forming of global human civilization, numerous transnational and interregional conflicts, need for mutual understanding, cooperation and partnership have determined the relevance of the dialogical form of communication, which has led to a deepening of dialogue not only human thinking but also its civilized existence. The dialogical thinking is necessary for overcoming ideological stereotypes, the monopoly of thought and one-sidedness of globalism, for the forming of a person who would be able to build his relationship on the basis of humanization, finding a reasonable compromise, mutual respect, and tolerance. In the context of conceptual positions of modern rhetoric, the phenomenon of rhetorical dialogue as a unit of rhetorical communication is singled out. It is worth considering the rhetorical dialogue in the prospection of a relativistic aspect of modern rhetoric, taking into account the pragmatic sense of the influence of communicators on each other in the process of harmonizing dialogue, effective and optimal communication. That’s why the intercultural dialogue in the process of forming of multilingual personality is defined as rhetorical. In the giving article, the subject of the discussion is highlighting the relevance of the intercultural dialogue as rhetorical on language lessons at schools with polyethnic contingent of pupils, clarification of the main aspects of dialogic interaction of contacting cultures, analysis of groups of national and specific vocabulary for learning by pupils-polylinguals.